DETERMINANTS OF INCOME INEQUALITY IN EU CANDIDATE COUNTRIES: A PANEL ANALYSIS - Bucevska, Vesna (The Faculty of Economics in Niš, 2019)
Despite increasing income per capita, the EU candidate and potential candidate countries remain confronted with high levels of income inequality. The purpose of our paper is to identify the main determinants of income inequality among the EU candidate countries. In addition to macroeconomic factors, we also analyze the impact of demographic variables to provide more reliable estimates. Using panel data analysis with fixed effects in the period 2005-2017 for three EU candidate countries (North Macedonia, Serbia and Turkey) we find that the unemployment rate, the level of economic development and the investment rate are the main determinants whose increase leads to a bigger income differentiation in the analyzed countries. The government indebtedness has also a statistically significant, but a negative impact on income inequality. The other two macroeconomic variables in the model – the terms of trade and inflation are statistically insignificant. Among the demographic factors, population growth and education significantly affect income inequality among the EU candidate countries. The obtained results suggest that a sustainable economic growth combined with active measures in the labor market and the improvement of education level of the population could lead to more equal income distribution.
Keywords: income inequality, panel data, macroeconomic factors, demographic factors, EU candidate countries